Determination of quality standards and evaluation of In vitro Antibacterial activity of Kanchanara Guggulu: An ayurvedic formulation - Guruvaurappan Palanichamy; Manas Ranjan Sahoo; Ramesh Raghava Varrier; Anithakumari Rajendran; Mageswari Harekrishna; Bala- Tirupurasundari Vijayashankar; S Srikrishna (Wolters Kluwer Medknow Publications, 2023)
Introduction: Ayurveda is one of the most renowned Indian traditional health-care systems and has been adopted globally in recent decades. In Ayurveda Kanchanara guggulu (KG) tablet is one of the Indian traditional medicines used in the treatment of various indications such as tonsilitis, cyst, abdominal lump, and fistula-in-ano. Methods: In the present study, KG tablet was prepared and standardized on basis of physical, physico-chemical properties, high-performance thin-layer chromatography (HPTLC) fingerprint, and phytochemical analysis. Heavy metal test of lead, arsenic, mercury, and cadmium was carried out to confirm the permissible limit as per the AYUSH and WHO standards. The antibacterial activity of the KG tablet was evaluated on two human pathogenic bacteria Escherichia coli and Staphylococcus aureus. Results: The heavy metal limit was found below the limit of quantification and within the allowable limit as per the AYUSH and WHO standards. The tablet showed comparable antimicrobial activity against both strains. The tablets were found to be having satisfactory quality parameters such as hardness, disintegration test, and friability values as per the pharmacopeia standards. Conclusion: The tested parameters based on the present study can be used as a reference approach for quality control of KG formulation. The HPTLC study was found to be an effective tool for quality control of herbal formulation to check the inter-batch batch consistency of the formulation. The antimicrobial activity against human pathogens substantiates its traditional uses.